Conference 18th Balcanicum: "Balkans from close-up and the distance " Poznan, 25-26th October 2019 - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2020)
A conference "18th Balcanicum: Balkans from close-up and the distance" was held in Poznan, 25-26th October 2019 and was organised by The Commission of the Balkan Studies of the Polish Academy of Sciences and Institute of History of Adam Mickiewicz University in Poznan. This paper summarizes the proceedings of the conference.